2014
DOI: 10.1080/08998280.2014.11929037
|View full text |Cite
|
Sign up to set email alerts
|

Sedation Levels During Propofol Administration for Outpatient Colonoscopies

Abstract: The levels of sedation required for patients to comfortably undergo colonoscopy with propofol were examined. One hundred patients undergoing colonoscopy with propofol were enrolled. In addition to standard-of-care monitoring, sedation level was monitored with the Patient State Index (PSI) obtained from a brain function monitor, transcutaneous carbon dioxide (tcpCO2) was monitored with the TCM TOSCA monitor, and end-tidal carbon dioxide was monitored via nasal cannula. The Ramsay Sedation Score (RSS) was also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…In addition, the blinded to PSI group was maintained at a deeper sedation level with more respiratory compromise than the unblinded group. This report demonstrated that propofol sedation delivered by a bolus technique was frequently taken to levels of general anesthesia [6] .…”
Section: Intermittent Bolus Administrationmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, the blinded to PSI group was maintained at a deeper sedation level with more respiratory compromise than the unblinded group. This report demonstrated that propofol sedation delivered by a bolus technique was frequently taken to levels of general anesthesia [6] .…”
Section: Intermittent Bolus Administrationmentioning
confidence: 82%
“…It is often taken to the level of general anesthesia and is at risk for respiratory depression and hemodynamic instability. The levels of sedation required for patients to comfortably undergo colonoscopy with propofol were assessed [6] . The sedation level was monitored with the Patient State Index (PSI), and end-tidal carbon dioxide was monitored via nasal cannula.…”
Section: Intermittent Bolus Administrationmentioning
confidence: 99%
“…This difference may be due that propofol lacks any analgesic activity and so a high dose is required to perform a painful procedure. [ 11 ] This usually results in a deep level of sedation, respiratory and cardiac depressions. [ 11 ] When propofol sedation is administered by nonanesthesia personnel, the incidence of occurrence of GA (or a deeper sedation level) may reach up to 88%.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] This usually results in a deep level of sedation, respiratory and cardiac depressions. [ 11 ] When propofol sedation is administered by nonanesthesia personnel, the incidence of occurrence of GA (or a deeper sedation level) may reach up to 88%. This increases the risk of respiratory depression, airway obstruction, and hemodynamic instability.…”
Section: Discussionmentioning
confidence: 99%
“…European guidelines recommend using fast-and short-acting drugs and monotherapy, and avoiding the use of IV-achieved pain relief [3]. Sedation from midazolam and opioids were earlier the standard, but for more than a decade and for a variety of procedures, the use of propofol has been welldocumented for endoscopy [4][5][6], dental treatment [7][8][9], renal stone therapy [10][11][12] and emergency care [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%